Penyuluhan Eksistensi Pemerintahan Desa Adat Dan Desa Administrasi Pada Persekutuan Riring, Rumahsoal, Ambon (PRRA) - Makaruku, Alfian Reymon; Ajawaila, Della P.; Sahetapy, Firel E.; Wattimury, Eivandro (Penerbit Widina, Widina Media Utama, 2025)
This community service activity was carried out with the aim of enhancing the understanding of the younger generation of the Riring, Rumahsoal, Ambon Fellowship (PRRA) regarding the existence of traditional village governments and administrative villages. Traditional villages represent the original form of local governance based on ancestral rights and customs, while administrative villages are developed from communities with limited potential and capacity, thus integrated into supra-village governmental structures. The method employed was Participatory Action Research (PAR) combined with the principles of Community-Based Research (CBR), which included stages of coordination with partners, participatory counseling, interactive discussions, and joint reflection. The results showed an increased knowledge among participants concerning the distinctions between traditional and administrative villages, along with a growing critical awareness of the importance of preserving traditional village rights. This program demonstrates that participatory approaches can serve as an effective means of community empowerment, as they not only deliver information but also foster collaboration and collective awareness in strengthening local identity.ABSTRAKKegiatan pengabdian kepada masyarakat ini dilaksanakan dengan tujuan meningkatkan pemahaman generasi muda Persekutuan Riring, Rumahsoal, Ambon (PRRA) mengenai eksistensi pemerintahan desa adat dan desa administrasi. Desa adat merupakan bentuk asli pemerintahan lokal yang mengedepankan hak asal-usul dan tradisi, sedangkan desa administrasi berkembang dari desa yang memiliki keterbatasan potensi dan kapasitas sehingga berada dalam struktur pemerintahan supra desa. Metode yang digunakan adalah Participatory Action Research (PAR) yang dipadukan dengan prinsip Community-Based Research (CBR), melalui tahapan koordinasi dengan mitra, penyuluhan partisipatif, diskusi interaktif, serta refleksi bersama. Hasil kegiatan menunjukkan adanya peningkatan pengetahuan peserta terkait perbedaan karakteristik desa adat dan desa administrasi, sekaligus tumbuhnya kesadaran kritis untuk menjaga dan melestarikan hak-hak tradisional desa. Kegiatan ini membuktikan bahwa pendekatan partisipatif mampu menjadi sarana pemberdayaan masyarakat, karena tidak hanya menyampaikan informasi, tetapi juga membangun kolaborasi dan kesadaran bersama dalam penguatan identitas lokal.